PENGARUH GAYA HIDUP DAN KELOMPOK REFERENSI TERHADAP MINAT MEMBELI ULANG (REPURCHASE INTENTION) (SURVEI PADA PELANGGAN THE KINGS RESTO KUPANG) - Bernadetha Ernayani Tae; Juita L. D Bessie (Universitas Kristen Wira Wacana Sumba, 2021)
This research aims to a) know the perception of the Lifestyle, Reference Group, and Repurchase Intention of customers at The Kings Resto Kupang; b) knowing and explaining the simultaneously effect of Lifestyle and Reference Group towards the Repurchase Intention of customer in The Kings Resto Kupang; c) knowing and explaining partially effect of the Lifestyle and Reference Group towards the Repurchase Intention of customer in The Kings Resto Kupang. The independent variables in the study are Lifestyle and Reference Group, while the dependent variable is Repurchase Intention.¬¬The number of samples is 100 respondentswith the criteria who ever visited The Kings Resto Kupang at least twice.Samples were gained using accidental sampling technique. Data were collected using questionnaires, interviews, interview, and literature studies and internet exploration. Data analysis techniques used are quantitative descriptive, multiple linear regression analysis and hypothesis testing using the SPSS 16 application.Descriptive Analysis's results show that overall, the respondents gave high categorized perception assessment of Lifestyle variable and Repurchase Intention variable. While, variable Reference Group, the respondents gave middling category. From the results of Multiple Linear Regression Analysis found the mathematical equation: Y = 7,285 + 0,411X1 + 0,384X2. Both the F Test and t Test results show that simultaneously and partially, Lifestyle and Reference Group variable have a significant effect on Repurchase Intention. However, based on the value of Adjusted R2 shows the contribution of the variable Lifestyle and Reference Group to Repurchase Intention is 48,3%.While 51.7% is influenced by other variables outside the focus of this study.